Teaching profession is stressful: lesson learned from Heilongjiang Province - Hongyi, Xia; Abdul Aziz, Nor Azni (International Journal of Evaluation and Research in Education (IJERE), 2024)
Numerous studies have documented elevated levels of job-related stress among teachers worldwide. Prolonged exposure to high levels of stress among teachers ultimately results in career burnout, directly contributing to a decrease in teacher recruitment rates as well as the depletion of valuable teaching resources. This study’s objective is to examine the causes of work stress among primary school teachers in Heilongjiang Province, China, and to explore the strategies adopted by headmasters to reduce teachers’ work stress. This study adopts a qualitative research design. Semi-structured interviews were carried out with six respondents from two primary schools in Heilongjiang, China. The finding indicates that primary school teachers have great work pressure, mainly from the factors of workload, interpersonal relationships, salary, and personal development. Some feasible countermeasures were put forward to relieve the pressure which include the management should establish good interpersonal relationships and appropriate evaluation and incentive mechanisms. Teachers’ workload should be reduced, and unnecessary meetings and inspections should be reduced. Teachers should be guided to adjust their mentality and make reasonable career plans. This study concludes methods to alleviate work stress among teachers can be implemented through various means by school management.